Is your gender an issue - Gruta, Ellen Meneses; Ongkeko, Ellen; Parrel, Tessa ([Manila] Asian Social Institute Communication Center)
Looks at the role of men and women in developing countries, the Philippines, in particular, through interview with Sr. Mary John Mananzan and others.
VHS
Editor, Jorge de Guzman, Jr.; Interviewees: Sr. Mary John Mananzan, OSB, Susan Fernandez-Magno, Jobart Bartolome, Tin Bartolome, U.P.I.S., Ramon Magsaysay Cubao High School, PSBA, Q.C. selected students.
Keywords: Sex role -- Philippines; Feminism -- Philippines; Sex differences; Sociology